Environmental isolates of Citrobacter braakii that agglutinate with Escherichia coli O157 antiserum but do not possess the genes responsible for the biosynthesis of O157 somatic antigen. - Khan, A. (Cambridge University Press, 2003)
While searching for Escherichia coli O157 in the aquatic environment of Calcutta using an immunodetection procedure, we fortuitously detected five strains of Citrobacter braakii, which cross-reacted with the commercially available O157 polyvalent antiserum. The five C. braakii isolates gave positive results when a sensitive dot-ELISA was performed with E. coli O157 monoclonal antibody. Further, the O157 monoclonal antibody recognized the bands of proteinase K treated whole cells of lipopolysaccharide of all the C. braakii isolates. Apart from weak reactions with two or three of the DNA probes, all the C. braakii strains did not hybridize with the other probes spanning the minimum region required for O157 O-antigen biosynthesis. These strains did not possess any of the virulence genes that are commonly found in the Shiga toxin-producing E. coli (STEC) specially the serotype O157: H7. Therefore, it appears that the serological cross-reaction between C. braakii and E. coli O157 antiserum is based on structural mimicry between the O-polysaccharide of C. braakii and E. coli O157.